THE RELEVANCIES AND APPLICABILITY OF HUMAN RESOURCES ACCOUNTING IMPLEMENTATIONS UNDER HEGELIAN DIALECTIC - Marsha Baniita Firdlo (Universitas Brawijaya, 2012)
Abstract: The Relevancies and Applicability of Human Resources Accounting Implementations Under Hegelian Dialectic. The discourse on Human Resource Accounting has started as far as 1960s when Rensis Likert outlined the recognition of human resource on fi nancial reporting. However, controversies also emerge, mainly concerning about the concept measurement, absence of accounting standard, and assets defi nition. This research is aimed to analyze the debate between two opposing theories under Hegelian Dialectic. Analysis of the controversies through both literature review and empirical evidences are then utilized to formulate synthesis to facilitate relevant and applicable Human Resource Accounting implementations. Abstrak: Relevansi dan Aplikabilitas Implementasi Akuntansi Sumber Daya Manusia melalui Dialektika Hegel. Diskursus tentang Akuntansi Sumber Daya Manusia telah dimulai sejak 1960an sejak Rensis Likert menjelaskan pengakuan sumber daya manusia dalam pelaporan keuagan. Walaupun demikian, kontroversi tetap muncul, khususnya berkenaan dengan konsep pengukuran, ketiadaan standar akuntansi serta defi nisi aset. Riset ini ditujukan menganalisa perdebatan antara kedua teori yang beroposisi melalui dialektika Hegel. Kontroversi tersebut dianalisa melalui reviu literatur dan bukti empiris yang selanjutnya digunakan untuk memformulasikan sintesis untuk memfasilitasi implementasi akuntansi sumber daya manusia yang relevan dan dapat diaplikasikan.